Everyday English Conversation Test Book 3 - Stempleski, Susan; London, Andy (New York, USA Oxford university press, 2007)
Talk Time gives students the time to listen English and the time to talk with classmates. Every lesson builds confidence, Starting with simpls reptition and gradually building up to free speaking Practice
12
Keywords: English as a second language; English language -- Conversation and phrase book; English language -- Examinations; English language -- Grammar; English language -- Study and teaching